The role of preregistration and registered reports in improving research transparency and reproducibility - Ernst-Rasmussen, Peter Bonde (Henry Stewart Talks, 2025)
The process of preregistration and registered reporting in scientific publications, Impact on research transparency and credibility, Promoting interdisciplinary work, Common misconceptions